MANAJEMEN KOMUNIKASI BADAN LINGKUNGAN HIDUP KOTA YOGYAKARTA DALAM PENANGANAN LIMBAH PERAK DI KOTAGEDE - , RADITIA YUDISTIRA SUJANTO; , Prof. Dr. Nunung Prajarto, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Awareness of the dangers of waste in the environment is not always shared by everyone in a community. Awareness, of course, would be useless without action and change following it. Kotagede is an area that is quite famous for its silver crafts industry. Starting from a rough workmanship to the sale of silver crafts can be found in Kotagede. In 2004 BLH of Yogyakarta held a socializing program in Kotagede concerning the importance of managing silver-industrial waste properly and efficiently. It has become the responsibility of the BLH because it is included in the section of the duties and functions of BLH in terms of public services. At the last socializing program BLH failed to convince the attending audience. On the basis of that said above the researcher wanted to find out how BLH managed its communication management with the people in Kotagede regarding the awareness building of the importance of silver-industrial waste management for the safety and health of their own community and the environment. This research was conducted with exploratory qualitative approach, and with data collection methods including interviews and document study. The research method itself is a case study. This study uses the basic theories of communication and management, and also communication crisis. The researcher assessed that there was a crisis in the management of BLH communication throughout the whole process of the socializing program. The study found that there are some things that become obstacles during the formation of the socializing program, starting from the stage of 'planning' to stage 'controlling'. Broadly speaking, the problems that existed covered the decisions taken by the management team during the process of the program implementation, which were not based on cultural and social considerations in Kotagede. At the stage of 'organizing' the team was not considering the assignments on the basis of competence or expertise of its members, but rather on the basis of positions or organizational structure. In addition, on stage 'control', the program implementation team did not do reporting properly, did not do archiving properly, and did not do post-program monitoring either. Even so, it is not entirely that the researcher only found negative things or deficiencies during the course of the study. Through the findings and suggestions that the researcher attached at the end of this thesis, the researcher expects that BLH will re-implement their programs related to the problem in Kotagede where there exist the dangers of waste from the industry of silver and other metals, because the researcher hopes that BLH will not miss out much time when the next action from BLH would no longer be anticipatory but rather reactive to environmental conditions in the area of Kotagede.